2021
DOI: 10.1186/s40352-021-00146-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and suicidality among three subgroups of male sex offenders: results from an Australian prisoner cohort

Abstract: Objective Prisoners complete suicide and self-harm more frequently than members of the community. Sex offenders have been found to be at greater risk of engaging in these behaviours. This study examines the characteristics, prevalence, and predictors of self-harm and suicide attempts among: sex offenders that only victimise children (ChildSOs); adults (AdultSOs); or both (age-crossover polymorphous; PolySOs). Methods Data from three waves (1996, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One of the most at-risk populations for dual harm are those located in custodial settings ( Dixon-Gordon et al, 2012). Notably, for the research reported here, those with sexual convictions are at a higher risk of suicidality than those who received non-sexual, non-violent convictions (Gullotta et al, 2021).…”
Section: Introductionmentioning
confidence: 63%
“…One of the most at-risk populations for dual harm are those located in custodial settings ( Dixon-Gordon et al, 2012). Notably, for the research reported here, those with sexual convictions are at a higher risk of suicidality than those who received non-sexual, non-violent convictions (Gullotta et al, 2021).…”
Section: Introductionmentioning
confidence: 63%
“…Looking at the longitudinal section, only 7 inmates (including 1 woman) were not receiving any psychiatrically relevant medication during their incarceration prior to self-harm. Looking at the international literature, there is a correlation between (past) psychiatric medication and the risk of self-harm ( 28 , 29 ), so a possible risk factor can also be derived for the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatrists treating patients convicted of sexual offenses in prison do not routinely record traumatic events or symptoms of post‐traumatic stress disorder (PTSD), even though knowledge of a traumatic antecedent will enable a more holistic approach to care. The population of men convicted of sexual offenses is particularly at risk of suicidal behavior [67], but the frequency of suicidal ideation, self‐harm and suicide risk could not be analyzed in this population as it is not systematically recorded in the medical files. This is another limitation of our study.…”
Section: Discussionmentioning
confidence: 99%